John Woolman: More Than Just a Journal the Capacity of One Individual to Make a Difference - Lutz, Beth Anna (My University, 2009)
John Woolman was an influential Quaker who lived in pre-revolutionary America. He is best known for his autobiography, the Journal of John Woolman, first published in 1774. However, far more than just offering a glimpse into the time-period of colonial America, John Woolman?s life is an example of the potential for a single individual to bring about true reform. This paper will examine the life of John Woolman (1720-1772) and his efforts, both private and public, to stand up against slavery in the colonial United States. Woolman was a Quaker minister who was one of the early voices to speak out against slavery in America. He was influential in laying the groundwork for the unification of the Friends against slavery. This paper will chart John Woolman's influence in the Quaker abolition movement, and the further legacy of his accomplishments.
Keywords: Woolman, John, 1720-1772; Antislavery movements--United States--History--Colonial period, ca. 1600-1775; Quakers--United States--Biography; Reformers--United States--Biography